A Road Map for Empowering Undergraduates to Practice Service Leadership Through Service-Learning in Teams. (June 2015) - Snell, Robin Stanley; Chan, Maureen Yin Lee; Ma, Carol Hok Ka; Chan, Carman Ka Man
We present a road map for providing course-embedded service-learning team projects as opportunities for undergraduates to practice as service leaders in Asia and beyond. Basic foundations are that projects address authentic problems or needs, partner organization representatives (PORs) indicate availability for ongoing consultation, students receive a complete orientation to service leadership, and project themes align with course curricula. Infrastructure and support involves a bridge of interinstitutional commitment and trust, initial site visits, in-class project consultations, helping teams to form and to elect conveners, providing service leadership reporting templates, and requiring project reports as graded coursework assignments. Potential road blocks include diversion from genuine service needs, POR/data unavailability, free riders, and failure to connect the project to course content. A bridge of student commitment leads to four other ingredients for successful project experiences: a sense of progress toward making a difference, constructive student-POR learning relationships, distributed leadership and initiative-taking, and applying course material to gain insight, guide actions, and frame recommendations. Besides attaining course-level goals, desired outcomes are that students and PORs perceive that the project has delivered good service, and that students can explain their practices and development as service leaders. We present three qualitative case illustrations.